As implicações do teorema forte de Löweheim-Skolem na doutrina da relatividade ontológica de Quine - Júlio César da Silva (2024)
In this study, I propose to expand the understanding of the thought of philosopher Willard Van Orman Quine (1908-2000), particularly regarding the Löwenheim-Skolem theorem in its strong form, within the context of his doctrine of ontological relativity. To this end, I present the ontological implications of adopting the ZFC set theory as the foundational theory in the Quinean interpretation. This goal unfolded into an investigation of the conceptual and argumentative elements of Quine's metaphysical project, relating not only to the aforementioned ontological relativity but also to ontological reduction, as well as to the formal characteristics of classical first-order logic inherent to ZFC and the Löwenheim-Skolem theorem in its strong form.